Compatibility of Arable Crops Intercropped with Dalbergia sissoo for Sustainable Rainfed Agriculture - Subrahmanyam, M. V. R.; Bheemaiah, G.; Ismail, Syed (Indian Forester, 1996)
A field trial was initiated in the year 1991 on red sandy loam soils of Student's Farm, College of Agriculture, Rajendranagar, Hyderabad to study the compatibility of tree crop association in sissoo based agroforestry system under dry land situation. During two years of study (1991 and 1992), the yields of arable crops viz., sunflower, castor and red gram did not vary much in association with sissoo except during second year where the yields of red gram was reduced considerably. However, the mean yields of sunflower (4.38 q/ha) and castor (4.86 q/ha) when intercropped with sissoo where recorded on par with that of respective sole crops (4.48 and 4.77 qlha respectively). The gross returns were also found higher in sunflower and castor crops under intercropping as well as sole cropping when compared to that of redgram. The associated crops did not exert any inimical effects on growth of sissoo. But the rate of increment in growth of sissoo was decreased to some extent in association with redgram. Growing sissoo trees proved beneficial specially in improving the site by increasillg organic carbon and nitrogen substantially as compared to fallow land. The results revealed that growing of sissoo in association with arable crops provides sustainability to the traditional arable farming in dry regions.